FRI0315 Patterns of femoral head migration in osteoarthritis of the hip. (23rd January 2014) - Hui, M.; Abdulrahim, H.; Rees, F.; Doherty, S.; Maciewicz, R.; Muir, K.; Zhang, W.; Doherty, M.
Abstract : Background: Variations in the pattern of femoral head migration (FHM) in hip osteoarthritis (OA) was initially described by Resnick in 1975. The reasons for different patterns are unclear. Genetic and constitutional factors have been suggested. Objectives: (1) To determine whether the pattern of FHM associates with nodal and radiographic hand OA; (2) to determine whether FHM associates with age at symptom onset of hip OA, and (3) whether FHM is symmetrical between right and left hips in bilateral hip OA. Methods: Participants included men and women with hip OA recruited between 2002 and 2008 as part of the Genetics of Osteoarthritis and Lifestyle (GOAL) and Genetics of Osteoarthritis (GOA) studies. Anteroposterior views of the pelvis were obtained using a standardised protocol. Hip OA was defined radiographically as the presence of definite joint space narrowing (JSN) and definite osteophytes, equivalent to Kellgren-Lawrence ≥2. FHM was measured using the area of maximal JSN, recorded as superolateral, superior intermediate, superomedial, superior indeterminate, axial, medial or concentric. Nodal phenotype was defined clinically as Heberden's and/or Bouchard's nodes affecting at least 2 rays of each hand. Radiographic hand OA was defined by the presence of definite JSN and definite osteophytes in at least 2 joints of 2 rays in each hand. Logistic regression models were used to adjust for age, gender and body mass index (BMI). Adjusted odds ratios (aOR) and 95% confidence intervals (CI) were calculated for association. Results: 1438 cases of hip OA were identified (53% female), with a mean age of 69 years (range 45-90 years), and mean BMI 29 (range 15-59). 437 (30%) had Heberden's and/or Bouchard's nodes. Bilateral hip OA was present in 651 (45%). Radiographic hand OA was found to associate positively with superomedial FHM (aOR 2.34, 95% CI 1.36-4.04, p=0.002) and negatively with superolateral FHM (aOR 0.45, 95% CI 0.25-0.81, p=0.008). However, there was no association between nodal phenotype and FHM. The age of symptom onset of hip OA was associated with superolateral migration (aOR 1.65, 95% CI 1.03-2.66, p=0.039) in people aged between 41 and 50, and superomedial migration (aOR 2.20, 95% CI 1.38-3.52, p=0.001) in those aged ≥70 years after adjustment for gender and BMI.In those with bilateral hip OA, the migration patterns of right and left hips were symmetrical with respect to the broad categories: superior (466 v 470); axial (41 v 46); medial (12 v 11); and concentric (16 v 15), respectively. However, more detailed examination of which hip was affected first, defined by symptom or by severity, reveals a difference. The second hip affected was more likely to be of superolateral migration (aOR 0.68, 95% CI 0.50-0.93, p=0.014) and the first hip was more likely to be of superomedial pattern (aOR 1.72, 95% CI 1.21-2.45, p=0.003). Conclusions: The association of FHM with polyarticular hand OA defined radiographically, but not by nodes, may suggest that FHM is more likely to be associated with a systemic phenotype. Lateral FHM may be related to earlier symptom onset of hip OA. FHM in bilateral hip OA tends to be symmetrical, but discordance may be seen according to the sequence of onset, where the second hip affected tends be of superolateral migration, which may be explained by altered biomechanical stresses on the second hip. Disclosure of Interest: M. Hui: None Declared, H. Abdulrahim: None Declared, F. Rees: None Declared, S. Doherty: None Declared, R. Maciewicz Shareholder of: AstraZeneca, K. Muir: None Declared, W. Zhang: None Declared, M. Doherty: None Declared